Computed Tomography Findings of Pigmented Villonodular Synovitis in a Dog - Dempsey, Lara M.; Maddox, Thomas W.; Meiring, Thelma; Wustefeld-Janssens, Brandan; Comerford, Eithne J. (Veterinary and Comparative Orthopaedics and Traumatology, 2018)
Pigmented villonodular synovitis (PVNS) is a rare benign and usually monoarticular neoplastic lesion arising from the synovium, bursae and tendon sheaths in humans, horses and dogs. Categorization for PVNS in humans includes localized and diffuse forms of PVNS and tenosynovial giant cell tumour (TGCT), although histologically they are the same. The localized form is characterized by discrete nodular lesions, the diffuse form is often intra-articular, infiltrative, affecting the entire synovium with more aggressive behaviour and TGCT occurs along tendon sheaths. Computed tomography (CT) of PVNS is well described in humans but not documented in the veterinary literature. Pigmented villonodular synovitis is not a straightforward diagnosis and CT is useful to further characterize radiographic findings. A representative open surgical biopsy of the synovium is essential to obtaining the diagnosis and ruling out malignancy. Currently, there are no guidelines for the diagnosis of PVNS in dogs or long-term follow-up of these cases. This case report describes the presentation, diagnostic findings, treatment and long-term outcome of a 4-year-old male Labrador Retriever with confirmed PVNS. Clinical outcome was considered fair with the dog's lameness and symptoms remaining stable with medical management 3 years following the initial diagnosis.
Keywords: shoulder; synovitis; dog; neoplasia; villonodular